Geo-Augmented Reality untuk Meningkatkan Spatial Thinking di TK Pembangunan Laboratorium UNP - Rahmaini, Aulia; Yulfa, Arie (Darul Yasin Al Sys, 2023)
Children’s spatial thinking by introducing geography through photos, maps, and building the ability to translate visualizations from pictures and video games, is very possible from preschool age. Preschool education is the basis for the development of all children’s abilities and intelligence. When we instill the basics of geography or natural landscape starting from preschool level, the child’s intelligence and ability level in the future will be even better. The aim of this research is to examine Geo-Augmented Reality learning media on preschool students’spatial thinking. The type of research is quantitative descriptive research. The data analysis technique in this research is the descriptive analysis method. The results of questionnaire data analysis show that Geo-Augmented Reality helps teachers in learning. The t-test results showed that Geo-Augmented Reality media had an effect on preschool students’ spatial thinking with a significance result of 0.000.